2018
DOI: 10.3390/molecules23092357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tea Catechins on Alzheimer’s Disease: Recent Updates and Perspectives

Abstract: Alzheimer’s disease (AD) is one of the most common neurodegenerative disorders worldwide. Its incidence is gradually increasing because of an aging demographic. Therefore, AD prevention and modification is important to improve the health status of older adults. Oxidative stress is a component of the pathological mechanisms underlying AD. It is caused by a disruption of the balance between reactive oxygen species and antioxidant molecules. This imbalance also causes neuroinflammation. Catechins, which are bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 93 publications
(101 reference statements)
0
45
0
Order By: Relevance
“…An association between the consumption of tea, rich in catechins, and the reduced risk of AD have been reported. Tea has been suggested to have anti-amyloid effects [43] and ameliorate cognitive dysfunction [44]. These effects have been mainly ascribed to the antioxidant and anti-inflammatory effects of tea catechins, but the inhibition of acetylcholinesterase by EGCG may contribute to this effect.…”
Section: Discussionmentioning
confidence: 99%
“…An association between the consumption of tea, rich in catechins, and the reduced risk of AD have been reported. Tea has been suggested to have anti-amyloid effects [43] and ameliorate cognitive dysfunction [44]. These effects have been mainly ascribed to the antioxidant and anti-inflammatory effects of tea catechins, but the inhibition of acetylcholinesterase by EGCG may contribute to this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a double-blind controlled study, type 2 diabetes patients had improvements in obesity and glucose levels after 582.8 mg or 96.3 mg consumption of catechins for 12 weeks [235]. Bone health improvements and Alzheimer's disease prevention by catechins in pre-clinical and clinical studies were summarized somewhere else [236,237].…”
Section: Catechinsmentioning
confidence: 99%
“…Moreover, the authors demonstrated that the levels of lipid peroxides in the hippocampus and plasma, and ROS were over 20% lower than in the control group. The antioxidative properties of catechins result from both their radical activity and their ability to chelate the prooxidative Fe 3+ ad Cu 2+ ions (which inhibits Fenton's reaction) [126]. It is known that said ions accumulate in the brains of patients suffering from AD [127].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Clinical studies pertaining to antioxidative therapies with potential application to neurodegenerative diseases have been very intensive in the recent years. In 2018 alone, in the USA and many European and Asian countries, over 10 clinical studies were conducted that pertained solely to the impact of catechins on the development of AD [126]. Simultaneously, other antioxidants and other neurodegenerative diseases are also being analyzed.…”
Section: Antioxidative Therapies In Neurodegenerative Diseases-clinicmentioning
confidence: 99%